Evaluation of the additional public infrastructures during the execution of the construction (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objective of this research is to evaluate the Additional Services during the execution of Public Works; because a significant percentage of their contracts are affected, it was identified and analyzed so that the research proposes measures to be applied to improve the procedure in the preparation of technical files, to eliminate the most frequent errors found in the last five years. The results showed that the highest incidence for additional services was 14.22%, and the lowest was -10.46%. The evaluation concluded that one of the leading causes with the highest incidence in the approval of additional work services is the deficiencies in the technical files.